The Influence of Project-Based Learning Models on Interpersonal Intelligence of Children Aged 5-6 Years at Kemala Bhayangkari 07 Gowa Kindergarten - Nur Fasira; Rusmayadi; Sri Rika Amriani H. (EduLine: Journal of Education and Learning Innovation, 2024)
This study aims to determine the effect of project-based learning model on interpersonal intelligence of children aged 5-6 years in Kemala Bhayangkari 07 Gowa Kindergarten before and after treatment and to determine whether or not there is an effect of project-based learning model on interpersonal intelligence of children aged 5-6 years in Kemala Bhayangkari 07 Gowa Kindergarten. The research approach used is a quantitative approach with a type of Quasi Experiment research. The independent variable in this study is the project-based learning model and the dependent variable in this study is interpersonal intelligence. The population in this study were 82 children, namely all students in group B. Sampling in this study using purposive sampling. The sample in this study were 60 children, 30 control group children and 30 experimental group children. The data analysis technique used is descriptive statistical analysis and parametric statistical analysis. The results of data analysis obtained a significant value of 0.000 <0.05 which means H0 and H1 are accepted, meaning that the interpersonal intelligence of children in the experimental group is better than the control class, this proves that the project-based learning model has a significant effect on the interpersonal intelligence of children aged 5-6 years at Kemala Bhayangkari 07 Gowa Kindergarten.